A system dynamics analysis about the recycling and reuse of new energy vehicle power batteries: an insight of closed-loop supply chain. Issue 1 (May 2020) - Yang, Jian; Mu, Dong; Li, Xin
Abstract: In order to solve the problem about recycling and reuse of power batteries for new energy vehicles in China, the paper, from the perspective of closed-loop supply chain (CLSC), uses VENSIM software to construct the system dynamics model. By analyzing the degree of cooperation among enterprises in CLSC, the result indicates that through cooperating with foreign excellent enterprises and enhancing the degree of cooperation among enterprises in the CLSC, the development of new energy vehicle power battery recycling can be better promoted. In addition, this paper puts forward some reasonable suggestions on the development of new energy vehicle power batteries.